Transformation Framework Design on Digital Copyright Entities Using Blockchain Technology - Tuti Nurhaeni; Leli Nirmalasari; Adam Faturahman; Sella Avionita (Blockchain Frontier Technology, 2021)
This research is based on the national need to build an effective HKI protection system. Results in the form of human intellectual work that have very high values ​​should receive adequate regulatory protection supported by a sense of justice & be rewarded according to their intellectual output. Copyright protection for creators and copyright holders according to Law Number 28 of 2014 concerning Copyright. Article 1 number 1 & Article 24 paragraph (1) & (2). So according to the parallel growth of science and the number of outputs of work found and technology which is very rapid, has a great effect on human life. With this background, this research adopts a research framework capable of compiling insights from current research bodies on blockchain technology. The application of the blockchain framework aims to make it easier for creators to prove what and when their work was made in front of a court or when registering a work copyright. Blockchain can provide solutions in copyright protection and digital copyright management.